Mean Value Theorem and Pohozaev Type Identities of Generalized Greiner Operator and Their Applications (Journal of Partial Differential Equations, 2001)
In this paper, a fundamental solution at the origin and mean value theorem of generalized Greiner operator are given. Then the Hardy type inequality and some Pohozaev type identities are proved. As their applications, some nonexistence results of semilinear nonelliptic equation and unique continuation are discussed.
Keywords: Fundamental solution; mean value theorem; Hardy type inequality; Pohozaev type identity; nonexistence; unique continuation